The effects of different resistance training protocols on muscular strength and endurance development in children - Faigenbaum, A. D.; Westcott, W. L.; LaRosa, R.; Long, C. (Pediatrics, 1999)
Previous research has shown that children can increase their muscular strength and muscular endurance as a result of regular participation in a progressive resistance training program. However, the most effective exercise prescription regarding the number of repetitions remains questionable.